2018
DOI: 10.1038/s41586-018-0344-3
|View full text |Cite
|
Sign up to set email alerts
|

The outer membrane is an essential load-bearing element in Gram-negative bacteria

Abstract: Gram-negative bacteria possess a complex cell envelope that consists of a plasma membrane, a peptidoglycan cell wall and an outer membrane. The envelope is a selective chemical barrier that defines cell shape and allows the cell to sustain large mechanical loads such as turgor pressure. It is widely believed that the covalently cross-linked cell wall underpins the mechanical properties of the envelope. Here we show that the stiffness and strength of Escherichia coli cells are largely due to the outer membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
462
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(482 citation statements)
references
References 30 publications
18
462
0
2
Order By: Relevance
“…Given that daughter cell separation‐defective chains are sensitive to osmotic stress, we also hypothesized that the outer membrane (OM) may be compromised in the ∆2 LTG mutant, as the OM is an important structural and load‐bearing component of Gram‐negative bacteria (Rojas et al , ). Lysozyme typically cannot permeate the OM in sufficient quantities to cause damage to the Gram‐negative cell wall.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that daughter cell separation‐defective chains are sensitive to osmotic stress, we also hypothesized that the outer membrane (OM) may be compromised in the ∆2 LTG mutant, as the OM is an important structural and load‐bearing component of Gram‐negative bacteria (Rojas et al , ). Lysozyme typically cannot permeate the OM in sufficient quantities to cause damage to the Gram‐negative cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments are representatives of at least two biological replicates. and load-bearing component of Gram-negative bacteria (Rojas et al, 2018). Lysozyme typically cannot permeate the OM in sufficient quantities to cause damage to the Gram-negative cell wall.…”
Section: δ2 Ltg Mutations Results In Outer Membrane Perturbationsmentioning
confidence: 99%
“…Measuring the mechanical properties of the cell wall is a long-term endeavor in plant and microbial sciences. Methods to measure wall stiffness include Atomic Force Microscopy (AFM) (13), active cell bending or compression (7,8,14), and strain-stress assays through the modulation of turgor pressure (10,11,(15)(16)(17)(18). Those allow to extract a surface elasticity but are in general low-throughput, and importantly do not take into account putative global or local variations in wall thickness, thereby preventing to discern contributions from bulk material properties vs thickness to cell wall elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The prescience of his statement is evident by scores of ensuing publications. Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram‐positive bacteria, and between the peptidoglycan and the outer membrane of the Gram‐negative bacteria . Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram‐positive bacteria and with respect to lipopolysaccharide transport in Gram‐negative bacteria .…”
Section: Cell Envelope‐targeting Antibioticsmentioning
confidence: 99%
“…Intimate structural synergy is now recognized between the peptidoglycan and the teichoic acids of the Gram-positive bacteria, 76 and between the peptidoglycan and the outer membrane of the Gramnegative bacteria. 77,78 Indeed, new opportunities for antibiotic discovery have been identified that interfere with teichoic acid integration into the cell wall of Gram-positive bacteria 69,[79][80][81][82][83][84] and with respect to lipopolysaccharide transport in Gram-negative bacteria. [85][86][87][88][89][90] Within this universe of opportunity, we exemplify our own efforts toward the mechanistic and structural understanding of key enzymes of the bacteria with roles in cell envelope biosynthesis and antibiotic resistance.…”
Section: Cell Envelope-targeting Antibioticsmentioning
confidence: 99%